The role of national health insurance for achieving UHC in the Philippines: a mixed methods analysis - Konrad Obermann; Matthew Jowett; Soonman Kwon (Taylor & Francis Group, 2018)
Background: Achieving Universal Health Coverage (UHC) has by now become a key health policy goal in many countries and some form of National Health Insurance (NHI) is often used for this. The Philippines has had more than 50 years' experience with social health insurance and in 1995 established PhilHealth, the country's national health insurer. Objectives: Analyzing the role of the Philippine NHI scheme in moving towards UHC, identifying potential avenues for improvement as well as indicating challenges and areas for further development. Methods: This paper is based on a mixed methods approach including extensive literature search, data from PhilHealth and other sources, and key informant interviews with staff at PhilHealth, health care providers, and policy experts at national and international level. Results: Major achievements were the expansion of population coverage using an earmarked revenue source ('Sin Tax'), the introduction of the no-balance-billing to prevent co-payments, and the Health Facilities Enhancement Program to improve quality. The share of PhilHealth in total health expenditures is still only 14%, managing quality and cost of providers remains insufficient, the benefit coverage does not reflect the country's burden of disease, and financial protection for PhilHealth members is low. The UHC bill would provide a massive jump forward as all Filipinos would then be automatically enrolled in and thus entitled to the benefits of PhilHealth. Conclusions: For expanding a contribution-based NHI beyond formal employment there needs to be a large increase in budget transfers to cover for citizens unable to contribute. The Philippine UHC bill shifts from the idea of contribution leading to entitlement to the idea of citizenship leading to entitlement and can thus be seen as a paradigmatic change in thinking about NHI. There are three areas that we believe are of key importance in developing further NHI: (i) governance, (ii) financial impact, and (iii) strategic purchasing.